Can Topical Vancomycin Prevent Periprosthetic Joint Infection in Hip and Knee Arthroplasty? A Systematic Review - Wong, Murray T. (Clin Orthop Relat Res, 2021)
BACKGROUND: Periprosthetic joint infection (PJI) after hip and knee arthroplasty is a leading cause of revision surgery, inferior function, complications, and death. The administration of topical, intrawound vancomycin (vancomycin powder) has appeared promising in some studies, but others have found it ineffective in reducing infection risk; for that reason, a high-quality systematic review of the best-available evidence is needed. QUESTIONS/PURPOSES: In this systematic review, we asked: (1) Does topical vancomycin (vancomycin powder) reduce PJI risk in hip and knee arthroplasty? (2) Does topical vancomycin lead to an increased risk of complications after hip and knee arthroplasty? METHODS: A search of Embase, MEDLINE, and PubMed databases as of June 2020 was performed according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Studies comparing topical vancomycin in addition to standard infection prevention regimens (such as routine perioperative intravenous antibiotics) with standard regimens only in primary hip and knee arthroplasty were identified. Patients 18 years or older with a minimum follow-up of 3 months were included. No restrictions on maximal loss to follow-up or PJI definition were imposed. Studies were excluded if they included patients with a history of septic arthritis, used an antibiotic other than vancomycin or a different route of administration for the intervention, performed additional interventions that differed between groups, or omitted a control group. A total of 2408 studies were screened, resulting in nine eligible studies reviewing 3371 patients who received topical vancomycin (vancomycin powder) during a primary THA or TKA and 2884 patients who did not receive it. Groups were comparable with respect to duration of follow-up and loss to follow-up when reported. Study quality was assessed using the Newcastle-Ottawa scale, showing moderate-to-high quality for the included studies. The risks of PJI and overall complications in the topical vancomycin group were compared with those in the control group. RESULTS: One of nine studies found a lower risk of PJI after primary THA or TKA, while eight did not, with odds ratios that broadly bracketed the line of no difference (range of odds ratios across the nine studies 0.09 to 1.97). In the six studies where overall complications could be compared between topical vancomycin and control groups in primary THA or TKA, there was no difference in overall complication risks with vancomycin (range of ORs across the six studies 0.48 to 0.94); however, we caution that these studies were underpowered to detect differences in the types of uncommon complications associated with vancomycin use (such as allergy, ototoxicity, and nephrotoxicity). CONCLUSION: In the absence of clear evidence of efficacy, and without a sufficiently large evidence base reporting on safety-related endpoints, topical vancomycin (vancomycin powder) should not be used in routine primary THA and TKA. Adequately powered, multicenter, prospective trials demonstrating clear reductions in infection risk and large registry-driven audits of safety-related endpoints are required before the widespread use of topical vancomycin can be recommended. LEVEL OF EVIDENCE: Level III, therapeutic study.